PENGEMBANGAN E-MODUL INTERAKTIF PADA MATERI TERMOKIMIA DI SMA NEGERI 3 KOTA BENGKULU - Rifki Nomizar; Hermansyah Amir; Salastri Rohiat (ALOTROP, 2023)
This study aims to develop teaching materials in the form of an Interactive E-Module on Thermochemistry at SMA Negeri 3 Bengkulu City. The feasibility of this Interactive E-Module is based on the assessment of media experts and material experts. Products that are declared feasible, are known to be attractive based on a questionnaire response to the interest of students and teachers. This type of research is Research and Development (R&D) with the ADDIE type of research model. There are 2 media and material validators each who are competent in their fields. The small-scale test sample was 12 students with purposive sampling technique and for the teacher's interest response test as many as 3 chemistry teachers. The results of the feasibility of the interactive E-Module are based on the assessment of media experts getting very valid qualifications with an average percentage of 94.50%, material validation getting very valid qualifications with an average percentage of 93.88%, student responses getting very interesting qualifications with an average percentage of 91.41% and the teacher's response to getting very attractive qualifications with an average percentage of 90.55%. This shows that the interactive E-Module on the thermochemical material produced in this study is considered very feasible to be used in learning.